The Dividend Policy as a Moderator of the Effect of Ownership Structure and Financial Performance on Firm Value - Abdul Bais; Titik Mildawati; Kurnia Kurnia (Akuntansi, 2026)
This study aims to analyze the moderating role of dividend policy in influencing the relationship between ownership structure, financial performance, and firm value. Specifically, the ownership structure is proxied by managerial ownership, institutional ownership, and foreign ownership, while financial performance is measured using profitability. Firm value is the dependent variable, and dividend policy is positioned as a moderating variable. The final dataset was analyzed using moderated regression analysis (MRA) to examine both direct effects and interaction effects between variables. The empirical results indicate that managerial ownership has a positive and significant effect on firm value, suggesting that higher managerial shareholding aligns managerial interests with shareholders, thereby improving company performance and market perception. Similarly, institutional ownership shows a positive and significant effect on firm value, indicating that institutional investors play an effective monitoring role in enhancing corporate governance and market confidence. In addition, profitability is found to have a positive and significant effect on firm value, implying that firms with higher profitability tend to be valued more highly by the market due to better financial performance and future growth prospects. However, dividend policy is found to moderate the relationship between profitability and firm value, indicating that dividend distribution strengthens the effect of profitability on firm value by signaling financial stability and reducing information asymmetry between management and investors. Overall, this study highlights that ownership structure and profitability are important determinants of firm value, while dividend policy plays a selective moderating role depending on the financial condition of the company.